Organ-specific small non-coding RNA responses in domestic (Sudani) ducks experimentally infected with highly pathogenic avian influenza virus (H5N1). Issue 1 (2nd January 2020) - Samir, Mohamed; Vidal, Ramon O.; Abdallah, Fatma; Capece, Vincenzo; Seehusen, Frauke; Geffers, Robert; Hussein, Ashraf; Ali, Ahmed A. H.; Bonn, Stefan; Pessler, Frank
ABSTRACT: The duck represents an important reservoir of influenza viruses for transmission to other avian and mammalian hosts, including humans. The increased pathogenicity of the recently emerging clades of highly pathogenic avian influenza (HPAI) viruses of the H5N1 subtype in ducks features systemic viral spread and organ-to-organ variation in viral transcription and tissue damage. We previously reported that experimental infection of Sudani ducks ( Cairina moschata ) with an Egyptian HPAI (H5N1) virus (clade 2.2.1.2) features high viral replication and severe tissue damage in lung, but lower viral replication and only mild histological changes in brain. Little is known about the involvement of miRNA in organ-specific responses to H5N1 viruses in ducks, and involvement of the other classes of small noncoding RNA (sncRNA) has not been investigated so far. Following RNA sequencing, we have annotated the duck sncRNome and compared global expression changes of the four major sncRNA classes (miRNAs, piRNAs, snoRNAs, snRNAs) between duck lung and brain during a 120 h time course of infection with this HPAI strain. We find major organ-specific differences in miRNA, piRNA and snoRNA populations even before infection and substantial reprogramming of all sncRNA classes throughout infection, which was less pronounced in brain. Pathway prediction analysis of miRNA targets revealed enrichment of inflammation-, infection- and apoptosis-related pathways in lung, but enrichment of metabolism-related pathways (including tryptophan metabolism) in brain. Thus, organ-specific differences in sncRNA responses may contribute to differences in viral replication and organ damage in ducks infected with isolates from this emerging HPAI clade, and likely other strains.